Modification of magnetic nanoparticle lipase catalyst with impregnation of Activated Carbon Oxide (ACO) in biodiesel production from PFAD (Palm Fatty Acid Distillate). (September 2022) - Buchori, Luqman; Widayat, W.; Hadiyanto, H.; Satriadi, Hantoro; Chasanah, Niswatun; Kurniawan, Muhammad Rizqi
Abstract: The production of biodiesel using Palm Fatty Acid Distillate (PFAD) assisted by magnetic nanoparticle lipase catalyst impregnated with Activated Carbon Oxide (ACO) has been studied. This study aims to examine the use of a magnetic nanoparticle lipase catalyst impregnated with activated carbon oxide in the production of biodiesel through a simultaneous esterification-transesterification reaction. The catalyst was characterized by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Fourier-Transform Infrared Spectrometer (FTIR). The simultaneous esterification-transesterification reaction was carried out in the reactor at a temperature of 56 °C, the mole ratio of methanol:PFAD is 16:1, a catalyst weight of 2.216 % wt, and a reaction time of 6 h. The biodiesel yield obtained was 94.915 %. The biodiesel yield decreased with repeated use of the catalyst and the catalyst underwent morphological changes after three uses. Graphical abstract: Unlabelled Image Highlights: Magnetic nanoparticle lipase catalyst impregnated with Activated Carbon Oxide (ACO) Simultaneous esterification-transesterification reaction of PFAD into biodiesel using Fe3 O4 Lipase-ACO catalyst Magnetic nanoparticle lipase impregnated with ACO has a crystalline system. The biodiesel which is obtained in this study has good quality The biodiesel yield decreased with repeated use of the catalyst